Adsorption of Cadmium on Transcarpathian Clinoptilolite - V.O. Vasylechko; G.V. Gryshchouk; Yu.B. Kuz'ma; L.O. Lebedynets; O.Ya. Oliyarnyk (Adsorption Science & Technology)
The adsorption properties of Ukrainian Transcarpathian clinoptilolite towards aqueous cadmium(II) solutions under static and dynamic conditions have been investigated. It has been demonstrated that cadmium(II) ions are most effectively adsorbed from sulphate solutions. The value of the adsorption capacity of clinoptilolite increased as the concentration of cadmium(II) increased in solution. The dynamic adsorption capacity of clinoptilolite towards a cadmium(II) solution at pH 5.6 under optimum conditions [adsorbent modified by heating at 130–170°C for 2.5 h; diameter of zeolite grains equal to ca. 0.20–0.31 mm; rate of flow of cadmium(II) solution of 500 ng/ml concentration through adsorbent equal to 3 ml/min] was 1.25 mg/g, while at pH 10.5 this was 3.0 mg/g. The optimal mixture for the desorption of cadmium was found to be 14 volumes of HCl (1:2) to 1 volume of conc. HNO 3 . The extraction of cadmium under these conditions was 95%.